Breast cancer but not the menopausal status is associated with small changes of the gut microbiota - Zeber-Lubecka, Natalia; Kulecka, Maria; Jagiełło-Gruszfeld, Agnieszka; Dąbrowska, Michalina; Kluska, Anna; Piątkowska, Magdalena; Bagińska, Katarzyna; Głowienka, Maria; Surynt, Piotr; Tenderenda, Michał; Mikula, Michał; Ostrowski, Jerzy (Frontiers in Oncology, 2024)
Background. Possible relationships between gut dysbiosis and breast cancer (BC) development and progression have been previously reported. However, the results of these metagenomics studies are inconsistent. Our study involved 88 patients diagnosed with breast cancer and 86 cancer-free control women. Participants were divided into groups based on their menopausal status. Fecal samples were collected from 47 and 41 pre-and postmenopausal newly diagnosed breast cancer patients and 51 and 35 pre-and postmenopausal controls, respectively. In this study, we performed shotgun metagenomic analyses to compare the gut microbial community between pre-and postmenopausal BC patients and the corresponding controls.Results. Firstly, we identified 12, 64, 158, and 455 bacterial taxa on the taxonomy level of phyla, families, genera, and species, respectively. Insignificant differences of the Shannon index and βdiversity were found at the genus and species levels between pre-and postmenopausal controls; the differences concerned only the Chao index at the species level. No differences in α-diversity indexes were found between pre-and postmenopausal BC patients, although β-diversity differed these subgroups at the genus and species levels. Consistently, only the abundance of single taxa differed between pre-and postmenopausal controls and cases, while the abundances of 14 and 23 taxa differed or tended to differ between premenopausal cases and controls, and between postmenopausal cases and controls, respectively. There were similar differences in the distribution of enterotypes. Of 460 bacterial MetaCyc pathways discovered, no pathways differentiated pre-and postmenopausal controls or BC patients, while two and one pathways differentiated cases from controls in the pre-and postmenopausal subgroups, respectively.While our findings did not reveal an association of changes in the overall microbiota composition and selected taxa with the menopausal status in cases and controls, they confirmed differences of the gut microbiota between pre-and postmenopausal BC patients and the corresponding controls. However, these differences were less extensive than those described previously.